Taunton Iron Works Co.; J.R. Williams, Fire Brick; H. Allen, Moving; L. Brynes, Fancy Turnings - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of Taunton Iron Works Co.; J.R. Williams, Fire Brick; H. Allen, Moving; L. Brynes, Fancy Turnings from the 1870 Boston City Directory